DIALEKTIKA KOMUNIKATIF ANTARA HAM INTERNASIONAL DAN HUKUM ISLAM - AL MUSTAANU (Indonesian Journal of Islamic Communication, 2018)
Human rights issues and Islamic world background for Mashood A. Baderin, although Islam is not a single factor in the realization of human rights in Muslim countries, but it becomes a very important factor that can be used as a means to realize the law. Islam as part of state law. The Harmonious Perspective is very helpful to use Islam as a means to realize human rights in the Muslim World in a socio-cultural and political-legal context, in order to promote and heal the common human rights. Mashood offers a narrative of the interaction between religion and international law, while it also offers an analysis of the effects that can be used to align the international field, and encourage the development of human rights. Concepts that affect every aspect of international relations and openness. This is the main purpose of the United Nations (UN). If we understand human rights as universal to protect individuals and people against violence, then the view that Islam is incompatible with human rights is due to the conversion and enhancement of human dignity in Islamic law.